2014
DOI: 10.1128/aac.01727-13
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Epidemiology and Mechanisms of Tigecycline Resistance in Clinical Isolates of Acinetobacter baumannii from a Chinese University Hospital

Abstract: bBecause of its remarkable ability to acquire antibiotic resistance and to survive in nosocomial environments, Acinetobacter baumannii has become a significant nosocomial infectious agent worldwide. Tigecycline is one of the few therapeutic options for treating infections caused by A. baumannii isolates. However, tigecycline resistance has increasingly been reported. Our aim was to assess the prevalence and characteristics of efflux-based tigecycline resistance in clinical isolates of A. baumannii collected fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
144
4
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 162 publications
(155 citation statements)
references
References 37 publications
6
144
4
1
Order By: Relevance
“…Tet(X) and Tet(56) are of particular interest due to their clinical significance. tet (X) has been recently identified in a number of human pathogens, including 11 nosocomial uropathogens from Sierra Leone 46 and 12 Acinetobacter baumannii isolates from a hospital in China 47 . We also showed that tet (56) is present and functional in L. longbeachae 28 – a pathogen responsible for causing Pontiac Fever and Legionnaires' Disease 32,33 .…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Tet(X) and Tet(56) are of particular interest due to their clinical significance. tet (X) has been recently identified in a number of human pathogens, including 11 nosocomial uropathogens from Sierra Leone 46 and 12 Acinetobacter baumannii isolates from a hospital in China 47 . We also showed that tet (56) is present and functional in L. longbeachae 28 – a pathogen responsible for causing Pontiac Fever and Legionnaires' Disease 32,33 .…”
Section: Resultsmentioning
confidence: 99%
“…These newer drugs are designed to evade resistance by efflux or ribosomal protection, but they are largely untested against tetracycline-inactivating enzymes. Alarmingly, tigecycline was found to be vulnerable to oxidative inactivation by Tet(X) 27 , which was recently identified for the first time in numerous pathogens of high clinical concern 46,47 . These challenges highlight the immediate importance of studying mechanisms of emerging tetracycline resistance, such as those described here that expand substrate scope.…”
Section: Discussionmentioning
confidence: 99%
“…In A. baumannii, the AdeABC efflux pump is the major efflux mechanism, and increased expression of the adeABC genes confers resistance to b-lactams, including carbapenems, aminoglycosides and tigecycline, and decreased susceptibility to fluoroquinolones, tetracycline, chloramphenicol, erythromycin, trimethoprim and netilmicin (Deng et al, 2014;Hou et al, 2012).…”
Section: Resultsmentioning
confidence: 99%
“…DNA extraction was performed using a QIAcube system (Qiagen), according to the instructions of the manufacturer. Detection by PCR was performed for OXA type (bla , bla OXA-24 , bla OXA-51 and bla OXA-58 ) carbapenemase genes (Woodford et al, 2006), and resistance genes associated with tigecycline (adeB, tetX1/tetX2) and colistin (pmrB) resistance (Bartha et al, 2011;Deng et al, 2014;Hou et al, 2012).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation